Evaluation of two-dimensional ultrasound fetal thymus size in correlation to infection parameters in pregnancies complicated with preterm premature rupture of membranes - Amal Kotb Abdallah; Mohamed Mohesen; Nagwan Kamal; Sahar Mahmoud Abd Elsalam; Sondos Salem; Ehab Salama; Mazen Abdel-Rasheed; Mohamed Eweis (Journal of the Arab Society for Medical Research)
Background/aim The thymus is essential for developing the fetal immune system and may show involution upon exposure to acute stress. Early detection of intrauterine infection is urgently needed to avoid fetal affection and sepsis. The present study aims to correlate the fetal thymus size with the infection parameters in pregnancies complicated with preterm premature rupture of membranes (PPROM). Subjects and methods The present study recruited pregnant women who fulfilled the inclusion criteria in a ratio of 1 case to 4 controls according to the study design; Group 1 of twenty cases presenting in PPROM, and Group 2 of eighty cases of women without PPROM. The primary outcome of the study was to measure fetal thymus size by abdominal ultrasound and its correlation with maternal total leukocytic count (TLC) and its differential count, C-reactive protein (CRP), and maternal fever. The secondary outcomes involved the correlation of the fetal thymus size with fetal distress, the occurrence of neonatal infection, Apgar neonatal score, and histological examination of the placenta and membranes for evidence of chorioamnionitis. Results Group 1 had a significantly higher CRP level (P<0.001), higher TLC level (P=0.035), and higher Staff (P<0.001). On the contrary, group 2 had significantly higher AFI (P=0.022), greater Thymus perimeter (P<0.001), and greater thymus transverse diameter (P<0.001). In addition, the pathological examination of the placenta revealed positive signs of infection in group 1 in only 65% of cases. Group 1 had a positive correlation between Thymus perimeter and APGAR score of the neonates (r=0.658, P=0.002), Thymus perimeter and birth weight (r=0.741, P<0.001), Thymus transverse diameter and APGAR score of the neonates (r=0.741, P<0.001), and finally Thymus transverse diameter and birth weight (r=0.734, P<0.001). Group 2 showed a significant positive correlation between the Thymus perimeter and neonatal APGAR score (r=0.232, P=0.039) and Thymus transverse diameter and birth weight (r=0.320, P=0.004). In Group 1, Cases with placental signs of infection (n=13) had higher CRP levels (P=0.046), higher TLC levels (P=0.014), higher Staff (P<0.001), but lower AFI (P=0.032). Conclusion The assessment of the fetal thymus during the routine second- and/or third-trimester scan could be a predictive measure for intra-amniotic infection. However, there is no association between small fetal thymus and adverse perinatal outcomes in uncomplicated pregnancies. Further larger studies with different demographic, maternal characteristics, and different inflammatory processes with and without active management to summarize whether fetal thymus can be used in clinical practice to avoid infection-related fetal morbidities or not.